2022
DOI: 10.3390/ma15031133
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties, Cytotoxicity, and Fluoride Ion Release Capacity of Bioactive Glass-Modified Methacrylate Resin Used in Three-Dimensional Printing Technology

Abstract: Background: Clinically, three-dimensional (3D) printing technology is becoming a popular and efficient dental processing technology. Recently, there has been an increasing demand for dental materials that exhibit bioactive properties. The present study aimed to evaluate the mechanical properties, cytotoxicity, and fluoride ion release capacity of 3D-printed dental resins modified with bioactive glass. Materials and methods: The resin FotoDent splint used in the production of removable orthodontic splints, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…An explanation of this phenomenon is provided in the article by Gad et al During printing, the resin is in contact with the air dissolved in it, particles of which can be obtained between the individual printed layers. This creates voids that can significantly reduce the bending resistance of the material [ 3 , 8 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An explanation of this phenomenon is provided in the article by Gad et al During printing, the resin is in contact with the air dissolved in it, particles of which can be obtained between the individual printed layers. This creates voids that can significantly reduce the bending resistance of the material [ 3 , 8 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This set-up was maintained in a humidified atmosphere at 37 C and 5% CO 2 . Microscopic observations were made after 1 h and 24 h of exposure to the tested articles (Leica DMi 1, CellService, Poznan, Poland) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keratinocytes were cultivated for 96 h and the cultures were then subjected to the cell viability MTT assay [ 44 ]. The cells were reacted with MTT and the color of the developed insoluble formazan product was read at 570 nm (Varioskan Flash; Thermo Fisher Scientific, Schwerte, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Raszewski et al [ 148 ] created novel dental materials for 3D printed orthodontic splints enriched with novel bioactive glass fillers of different compositions and assessed their physical properties, cytotoxicity effects, solubility, capacity to release fluoride ions, elution of nanpolymerized components, and their influence on cell cultures. The experiment results showed that modification of methacrylate resin, used in 3D printing technology, with bioactive glasses can produce novel dental materials that possess desirable bioactive properties.…”
Section: Emerging Trendsmentioning
confidence: 99%